The sea lice (Copepoda: Caligidae) of Moreton Bay (Queensland, Australia), with descriptions of thirteen new species - Boxshall, G.A. (Zootaxa, 2018)
Fifty species of sea lice, members of the family Caligidae, were collected from the marine fishes of Moreton Bay, Queensland, during two workshops held in 2016. Only 21 of these species had previously been reported from Australian waters: of the remaining 29 species, 13 are new to science and another 16 are recorded from Australia for the first time. An illustrated differential diagnosis is presented for well known species; but for new or poorly known species a full description is provided. The 13 new species are: Anuretes amplus sp. nov. and A. amymichaelae sp. nov., both from Diagramma pictum (Thunberg, 1792); Caligus abigailae sp. nov. from Sphyraena obtusata Cuvier, 1829; C. elasmobranchi sp. nov. from Himantura uarnak (Gmelin, 1789), H. toshi Whitley, 1939, Dasyatis fluviorum Ogilby, 1908, Aetobatus ocellatus (Kuhl, 1823) and Pastinachus atrus (Macleay, 1883); C. hyporhamphi sp. nov. from Hyporhamphus quoyi (Valenciennes, 1847); C. nataliae sp. nov. from Herklotsichthys castelnaui (Ogilby, 1897) and Neoarius graeffei (Kner & Steindachner, 1867); C. neoaricolus sp. nov. and C. paranengai sp. nov. both from Neoarius graeffei; C. pseudorhombi sp. nov. from Pseudorhombus arsius (Hamilton, 1822); C. turbidus sp. nov. from Tripodichthys angustifrons (Hollard, 1854); C. upenei sp. nov. from Upeneus tragula Richardson, 1846; Lepeophtheirus robertae sp. nov. from Scarus ghobbhan Forsskål, 1775 and Pupulina keiri sp. nov. from Aetobatus ocellatus. The rare species Caligodes alatus Heegaard, 1945 is redescribed and transferred to the genus Caligus Müller, 1785, but requires a replacement name due to secondary homonymy: Caligus alepicolus nom. nov. is proposed. Similarly, Parapetalus spinosus Byrnes, 1986 is redescribed and transferred to the genus Caligus where it becomes a secondary homonym: the replacement name Caligus seriolicolus nom. nov. is proposed. Five large species-groups within the genus Caligus are recognised here on the basis of suites of morphological character states. They are based around the following species: C. bonito Wilson, 1905, C. confusus Pillai, 1961, C. diaphanus von Nordmann, 1832, C. macarovi Gusev, 1951 and C. productus Dana, 1852. These species-groups can be used to navigate this relatively large genus, but their monophyletic status should not be assumed.